The role of extracellular vesicles in cancer - Perez Hurtado, Elizabeth Cristina; Henao Agudelo, Juan Sebastian; Foganholi da Silva, Rodrigo Augusto; Viração, Thiago Albuquerque; Fernandes, Célio Junior da Costa [UNESP] (Elsevier, 2024)
Extracellular vesicles (EVs), which include small EVs such as exosomes, play a critical role in intercellular communication and are produced by both cancer and non-cancer cells. Several studies have shown that cancer cells exploit various strategies to regulate the biogenesis, composition, and functions of EVs primarily to promote cancer progression. Given that exosomes originate from major sorting hubs at the limiting membrane of endosomes, they are central to a signaling network that connects external stimuli with intrinsic tumor cell features. Exosomes contain diverse repertoires of molecular cargos, such as proteins, lipids, and nucleic acids, which determine their heterogeneity and functional properties in cancer progression. Therefore, targeting exosome biogenesis will enhance our understanding of tumorigenesis and also promote the discovery of novel approaches for cancer therapy. In this chapter we summarize the machinery of exosome biogenesis and the local, distant, and systemic effects of exosomes released by cancer cells. Furthermore, we explore how these exosomes regulate the anti-tumor immune response and epigenetic mechanisms to sustain cancer progression and their implications in cancer prevention and treatment.
Keywords: Cancer progression; Cancer therapy; Cell communication; Epigenetic modifiers; Exosome; Immune surveillance; MicroRNAs; Rabs proteins; Small extracellular vesicles; Tumor microenvironment